2017
DOI: 10.5194/bg-14-5029-2017
|View full text |Cite
|
Sign up to set email alerts
|

Differential photosynthetic responses of marine planktonic and benthic diatoms to ultraviolet radiation under various temperature regimes

Abstract: Abstract. We studied the photophysiological responses to ultraviolet radiation (UVR) of two diatoms, isolated from different environmental niches. Both species showed the highest sensitivity to UV radiation under relatively low temperature, while they were less inhibited under moderately increased temperature. Under the highest temperature applied in this study, the benthic diatom Nitzschia sp. showed minimal sensitivity to UV radiation, while inhibition of the planktonic species, Skeletonema sp., increased fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The extent of the effect of UV radiation shows substantial variation among individual organisms. 80,242 In nature, the effects are dependent on the level of exposure to UV radiation, but they are also modulated by temperature 239,242 and nutrients (section 3.3). Since sensitivity to these effects also varies between species and with environment, exposure to UV radiation has the potential to change the composition of communities.…”
Section: Primary Producersmentioning
confidence: 99%
“…The extent of the effect of UV radiation shows substantial variation among individual organisms. 80,242 In nature, the effects are dependent on the level of exposure to UV radiation, but they are also modulated by temperature 239,242 and nutrients (section 3.3). Since sensitivity to these effects also varies between species and with environment, exposure to UV radiation has the potential to change the composition of communities.…”
Section: Primary Producersmentioning
confidence: 99%
“…Given the importance of diatoms to global primary production, how these organisms respond to nutrient limitation and UV radiation is of great importance. Previous work on nutrient limitation and UVR interactions under N and P limitation has been carried out on a green alga (35,42) However, the one study showing that nutrient limitation reduced the inhibitory effects of UV and high PAR was on an Antarctic diatom, in which the responses could be complicated by the effect of low temperature which may inhibit repair at low temperature (43,44). Our results revealed that photoinhibition induced by high light and UV radiation was more severe in diatom cells that were grown under limited nitrogen supply (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of UV‐induced damage to PSII ( k , min −1 ) and the repair rate ( r , min −1 ) under light exposure were calculated using the following Nonline fitting formula :PtP0=rk+r+kk+re(k+r)t,where P 0 is the initial effective quantum yield, and P t is the effective quantum yield after t minutes.…”
Section: Methodsmentioning
confidence: 99%
“…The recovery rate ( R , min −1 ) of P. yezoensis under dim light conditions was calculated by a fitting equation :y=y0+cfalse(1eαtfalse).…”
Section: Methodsmentioning
confidence: 99%